A Review of Research on Thick Translation - Qian, Yan; Chuanmao, Tian (International Journal of Humanities and Education Development (IJHED), 2020)
This article reviews the research on thick translation both at home and abroad by the documentary analysis method. It is found that, in spite of the outcomes obtained from existing theoretical and applied researches on thick translation, there are two aspects in need of improvement with regard to studying translated works with thick translation. On the one hand, the object of study is mainly literary works, without enough attention paid to texts of other types. On the other hand, discussion on the application of thick translation in specific translated works is limited to listing examples, with deep investigation into research results being ignored.